Experience of healthcare workers in combatting COVID-19 in Indonesia: A descriptive qualitative study - Ramadhan Tosepu; Joko Gunawan; Devi Savitri Effendy; Muhammad Rustam HN; Febriana Muchtar; Ambo Sakka; Diah Indriastuti (Belitung Raya Foundation, Indonesia, 2021)
Background: The number of COVID-19 cases in Indonesia continues to rise. The roles and responsibilities of healthcare workers are crucial in the battle of the COVID-19. Objective: This study aimed to explore the experience of healthcare workers in combatting COVID-19 in some parts of Indonesia. Methods: This study employed a descriptive qualitative study design. Online semi-structured interviews were conducted in April 2020 among thirteen participants who were purposively selected. Data were analyzed using thematic analysis. Results: Eight themes emerged from data, including lack of personal protective equipment, lack of referral hospitals and limited facilities, dealing with patients with unknown status, feeling worried about getting infected or being a source of viral transmission, being creative, too long shift and fatigue, being surrender to God, and government issues. Conclusion: Findings of this study could be used as the input for the government, healthcare workers, and the general population in combatting COVID-19.